TpiA is a Key Metabolic Enzyme That Affects Virulence and Resistance to Aminoglycoside Antibiotics through CrcZ in Pseudomonas aeruginosa - Xia, Yushan (mBio, 2020)
Carbon metabolism plays an essential role in bacterial pathogenesis and susceptibility to antibiotics. In Pseudomonas aeruginosa, Crc, Hfq, and a small RNA, CrcZ, are central regulators of carbon metabolism. By screening mutants of genes involved in carbon metabolism, we found that mutation of the tpiA gene reduces the expression of the type III secretion system (T3SS) and bacterial resistance to aminoglycoside antibiotics. TpiA is a triosephosphate isomerase that reversibly converts glyceraldehyde 3-phosphate to dihydroxyacetone phosphate, a key step connecting glucose metabolism with glycerol and phospholipid metabolisms. We found that mutation of the tpiA gene enhances the bacterial carbon metabolism, respiration, and oxidative phosphorylation, which increases the membrane potential and promotes the uptake of aminoglycoside antibiotics. Further studies revealed that the level of CrcZ is increased in the tpiA mutant due to enhanced stability. Mutation of the crcZ gene in the tpiA mutant background restored the expression of the T3SS genes and the bacterial resistance to aminoglycoside antibiotics. Overall, this study reveals an essential role of TpiA in the metabolism, virulence, and antibiotic resistance in P. aeruginosa.